Implementation Of Total Quality Management (TQM) In Madrasah: A Critical And Comprehensive Analysis Through Literature Study - Afriantoni; Rahma Alya, Kiki; Juni; Dania Zalyanti (Jurnal Manajemen Pendidikan Islam Darussalam, 2025)
This study aims to analyze the implementation of quality management in education at schools and Islamic schools in Indonesia through a literature review approach. Quality education is key to national development, and quality management plays a strategic role in improving teaching effectiveness, stakeholder satisfaction, and the professionalism of educators. This study focuses on the concept of Total Quality Management (TQM), which emphasizes continuous improvement, multi-stakeholder involvement, and consistent evaluation. The results of the literature review indicate that the success of TQM implementation is influenced by strong leadership, effective communication between stakeholders, performance rewards, and the integration of a quality culture at every level of the educational institution. The main obstacles faced are limited resources, a lack of understanding of TQM, and resistance to change. Several studies reviewed highlight the implementation of TQM in various Islamic educational units, such as Madrasah Tsanawiyah and Madrasah Aliyah, with generally positive results, although challenges related to operational costs and changes in organizational culture remain concerns. Successful strategies include unifying the vision and mission, strengthening student character, and providing maximum service to all stakeholders, including teachers, students, and parents. The implication of this research is the need to adopt an adaptive and contextual quality management system, accompanied by intensive training for all human resources in education. With the implementation of appropriate strategies, it is hoped that the quality of Islamic education in Indonesia will be continuously improved.